Influences of water molecules on the electronic properties of atomically thin molybdenum disulfide - Zhang, Kang (2017)
Although it is well known that the performances of two-dimensional transition metal dichalcogenide (2D-TMD) based devices are strongly affected by humidity, the roles of water molecules in the electronic properties of 2D-TMDs are still unclear. In this work, the influence of water molecules on the electrical properties of monolayer molybdenum disulfide (MoS2) is studied systemically using the dielectric force microscopy (DFM) technique. Taking the advantage of the DFM technique and other nondestructive characterization techniques, the electronic properties (surface potential, dielectrics, and carrier mobility) of atomically thin MoS2 exposed to different levels of humidity are investigated. Furthermore, Raman spectroscopy manifested the correlation between the optical phonon and the mobility drop of MoS2 flakes when subjected to humidity variations. Our results provide an in-depth understanding of the mechanism of water molecules interacting with MoS2.